MORALITY AND HAPPINESS IN ISLAM: A PHILOSOPHICAL STUDY OF THE CONCEPT OF SA'ADAH ANALYSIS OF AL-KINDI'S THOUGHT - Jannah, Meftahul; Tedy, Armin (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
This study is motivated by the importance of conceptual understanding of the relationship between morality and happiness (sa‘adah) in classical Islamic philosophy, particularly in the thought of Al-Kindi. In the context of modern life marked by moral decline and the search for existential meaning this research is relevant to revisiting profound philosophical values. Employing a qualitative method with a philosophical-analytical approach, the study is based on a literature review of Al-Kindi’s works and related sources. The findings reveal that Al-Kindi perceives true happiness not as worldly pleasure, but as a spiritual achievement attained through intellectual refinement, self-discipline, and ethical conduct. For Al-Kindi, morality is the primary path to achieving sa‘adah, as it enables the purification of the soul and alignment with ultimate truth and divine proximity. This research contributes to enriching Islamic philosophical discourse by highlighting the integration of intellect, ethics, and spirituality as the foundation of true happiness, and by demonstrating the continued relevance of Al-Kindi’s thought in addressing contemporary ethical and existential challenges.